2008
DOI: 10.1016/j.cub.2008.01.061
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Physical Interaction of Blue- and Red-Light Sensors in Aspergillus nidulans

Abstract: Light sensing is very important for organisms in all biological kingdoms to adapt to changing environmental conditions. It was discovered recently that plant-like phytochrome is involved in light sensing in the filamentous fungus Aspergillus nidulans[1]. Here, we show that phytochrome (FphA) is part of a protein complex containing LreA (WC-1) and LreB (WC-2) [2, 3], two central components of the Neurospora crassa blue-light-sensing system. We found that FphA represses sexual development and mycotoxin formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
341
3
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 279 publications
(359 citation statements)
references
References 24 publications
7
341
3
8
Order By: Relevance
“…This implies that loss/gain of function of FluG in asexual development has occurred at least two independent times in the evolution of aspergilli. We also showed that asexual development does not depend on light in the case of A. niger, while it preferentially takes place in the light in the case of A. nidulans (Purschwitz et al 2008) and is repressed by white and red light in A. oryzae (Hatakeyama et al 2007). Multiple copies of amyR were introduced in A. niger to assess whether over-expression of this regulator would impact production levels of glucoamylase and its spatial release in colonies.…”
Section: Discussionmentioning
confidence: 81%
“…This implies that loss/gain of function of FluG in asexual development has occurred at least two independent times in the evolution of aspergilli. We also showed that asexual development does not depend on light in the case of A. niger, while it preferentially takes place in the light in the case of A. nidulans (Purschwitz et al 2008) and is repressed by white and red light in A. oryzae (Hatakeyama et al 2007). Multiple copies of amyR were introduced in A. niger to assess whether over-expression of this regulator would impact production levels of glucoamylase and its spatial release in colonies.…”
Section: Discussionmentioning
confidence: 81%
“…The life cycle is light-dependent. During illumination, primarily green asexual spores (conidia) are formed on conidiophores, whereas the sexual structures are repressed by light and primarily formed in dark and under limited oxygen levels (Adams et al, 1998;Bayram et al, 2010;Braus et al, 2010Braus et al, , 2002Purschwitz et al, 2008). The closed sexual fruiting bodies (cleistothecia) are surrounded by nursing Hülle cells (Sarikaya Bayram et al, 2010) and contain the red ascospores.…”
Section: Introductionmentioning
confidence: 99%
“…The blue-light response often seems to be the most important one; e.g., all light-dependent processes in N. crassa are regulated by UV or blue light (13,14). In contrast, A. nidulans responds well to red light in addition to blue light (15,16). It was discovered recently that the blue-and red-light-sensing chromoproteins along with some additional proteins form a light-regulator complex in this fungus (17).…”
mentioning
confidence: 99%